PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS PROBLEM BESED LEARNING UNTUK MENINGKATKAN LITERASI SAINS SISWA PADA MATERI EKOSISTEM KELAS X SMA NEGERI 1 TOMA - Ganumba, Sanubari (Universitas Nias Raya, 2025)
This research aims to produce products in the form of problem-based learning modules that are valid, practical and effective. This type of research is the development of a four-D development model using research and development methods (Research and Development). Where the results of the validation carried out by the validator with an average value of 3.9 and a percentage value of 94% in the very valid category, the teacher's response to the problem based learning module with an average value of 3.5 in the very practical category, the results of the practicality test by students with an average score of 3.5 in the very practical category, the results of observations of student motivation with an average score of 3.5 in the very high category and the cognitive domain before using problem based learning modules with an average score of 66.6/pass while the cognitive domain using problem based learning based modules with an average score of 87.7/pass. So through these results it is concluded that the development of problem based learning based modules is valid, practical and effective, to support student learning outcomes. The researcher's suggestion is that biology subject teachers should be able to use this problem based learning-based module as teaching material in the teaching and learning process and through this teaching material hopefully students can broaden their insight into biology learning later, for future researchers so that this research can be used as reference material in relevant research.